MODEL PENDIDIKAN INKLUSI BAGI ANAK TUNAGRAHITA DI SEKOLAH DASAR - Supena., Asep (Pendidikan Dasar, 2009)
Abstract; The purpose of research is to obtain data comprehensively about how inclusive education for student with mental retardation can be conducted. There are seven research focus that be studed i.e. curriculum, learning goal, learning material, teaching plan, teaching management,  media and resource of learning and evaluation. Research be conducted by qualitative approach in one inclusive primary school in Bogor. Data be collected by depth interview and observation and document analysis. Result of study indicated that student with mental retardation can be educated together with normal student in regular school (class room). There are three condition that support the implementation of inclusive education for student with mental retardation. First, available government policy that support school for conducting inclusive education. Second, available positive attitude and behavior from school society toward inclusive education. Third, there are readiness technically from school to implement inclusive education. Modification is the importance key in implementing inclusive education. Research found that teachers do modification to amount component of learning in order to match with  capability of student with mental retardation, i.e curriculum, learning proses and evaluation.